## If sin(x+y)=3x−2y, then dydx=

### To find dy/dx given sin(x + y) = 3x – 2y, we will differentiate both sides of the equation with respect to x using the chain rule

To find dy/dx given sin(x + y) = 3x – 2y, we will differentiate both sides of the equation with respect to x using the chain rule.

First, let’s rewrite the equation to make it easier to differentiate:

sin(x + y) = 3x – 2y

Using the chain rule, we differentiate both sides of the equation with respect to x:

d/dx(sin(x + y)) = d/dx(3x – 2y)

To differentiate sin(x + y), we use the chain rule:

cos(x + y) * (d/dx(x + y)) = 3 – 0

Differentiating x with respect to x gives us 1, and differentiating y with respect to x gives us dy/dx.

cos(x + y) * (1 + dy/dx) = 3

Now, let’s isolate dy/dx by rearranging the equation:

cos(x + y) + cos(x + y) * dy/dx = 3

cos(x + y) * dy/dx = 3 – cos(x + y)

Finally, divide both sides by cos(x + y) to obtain the value of dy/dx:

dy/dx = (3 – cos(x + y)) / cos(x + y)

Therefore, the value of dy/dx is (3 – cos(x + y)) / cos(x + y).

##### More Answers:

The Intermediate Value Theorem | Exploring its Applications in Calculus and EquationsFinding the Derivative of the Inverse Function | A Step-by-Step Guide with Example Calculation

Finding the Slope of a Tangent Line | Step-by-Step Guide with Example